Site suitability study for recycling plastic plant / Hasbullah Hashim - Hasbullah, Hashim (2021)
Important site selection criteria include compatibility of land use and the adequacy of recycling of industrial plastics is a major industry in the country. Site suitability depends on the project's compatibility with local plans and gazette structures, as well as the surrounding land use and setbacks. The site was gazette for industry activity because of its topography and proximity to rubber plantations. Kota Trading, a manufacturer of natural rubber in 1960, owns the land. Important site selection criteria include the compatibility of land use and the adequacy of the buffer between the proposed industry and activity and its neighbours, as these factors allow the selection of environmental management options that avoid unnecessary investments in pollution control beyond what is normally required. Identifying the types of receptors that are sensitive and the primary criteria for site selection are principal factors in determining the best buffer for recycling plastic industries. If you want to choose the best buffer between a source and a receptor, you need to consider its nature, character, and response to an impact, among other factors. Buffer distances are prescribed based on the potential to affect the environment and the significance of the impacts on human health and environmental conservation, and the industry standard used for pollution control.